Transference-focused psychotherapy for borderline personality disorder: Change in reflective function. (August 2015) - Fischer-Kern, Melitta; Doering, Stephan; Taubner, Svenja; Hörz, Susanne; Zimmermann, Johannes; Rentrop, Michael; Schuster, Peter; Buchheim, Peter; Buchheim, Anna
Summary: Borderline personality disorder is associated with deficits in personality functioning and mentalisation. In a randomised controlled trial 104 people with borderline personality disorder received either transference-focused psychotherapy (TFP) or treatment by experienced community therapists. Among other outcome variables, mentalisation was assessed by means of the Reflective Functioning Scale (RF Scale). Findings revealed only significant improvements in reflective function in the TFP group within 1 year of treatment. The between-group effect was of medium size ( d = 0.45). Improvements in reflective function were significantly correlated with improvements in personality organisation.